Advances in the relationship between ferroptosis and epithelial–mesenchymal transition in cancer - Mu, Wenrong; Zhou, Zubang; Shao, Liping; Wang, Qi; Feng, Wanxue; Tang, Yuling; He, Yizong; Wang, Yuanlin (Frontiers in Oncology, 2023)
Epithelial-mesenchymal transition (EMT) is a cellular reprogramming process that converts epithelial cells into mesenchymal-like cells with migratory and invasive capabilities. The initiation and regulation of EMT is closely linked to a range of transcription factors, cell adhesion molecules and signaling pathways, which play a key role in cancer metastasis and drug resistance. The regulation of ferroptosis is intricately linked to various cell death pathways, intracellular iron homeostasis, and the protein network governing iron supply and storage. The ability of ferroptosis to disrupt cancer cells and overcome drug resistance lies in its control of intracellular iron ion levels.EMT process can promote the accumulation of iron ions, providing conditions for ferroptosis. Conversely, ferroptosis may impact the regulatory network of EMT by modulating transcription factors, signaling pathways, and cell adhesion molecules. Thus, ferroptosis related genes and signaling pathways and oxidative homeostasis play important roles in the regulation of EMT. In this paper, we review the role of ferroptosis related genes and their signaling pathways in regulating cancer EMT to better understand the crosstalk mechanism between ferroptosis and EMT, aiming to provide better therapeutic strategies for eradicating cancer cells and overcoming drug resistance.